2022
DOI: 10.1101/2022.09.08.506740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell cycle progression defects and impaired DNA damage signaling drive enlarged cells into senescence

Abstract: Cellular senescence plays an important role in development, ageing, and cancer biology. Senescence is associated with increased cell size, but how this contributes to permanent cell cycle exit is poorly understood. Using reversible G1 cell cycle arrests combined with growth rate modulation, we examined the effects of excess cell size on cell cycle progression in human cells. We show that enlarged cells paradoxically have high levels of G1/S regulators relative to cells that were maintained at physiological siz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 85 publications
0
34
0
Order By: Relevance
“…The lack of apparent DNA damage from cells withdrawing from G0/G1 is crucial (Crozier et al, 2022; Manohar et al, 2022; Wang et al, 2022) ( Supplementary Figure 4A ). Cells that enter S-phase and undergo replication stress will trigger a DNA damage response, which was demonstrated to activate NF-kappa-B and induce a secretory phenotype that promotes proliferation and migration of tumour cells (Chien et al, 2011; Rodier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of apparent DNA damage from cells withdrawing from G0/G1 is crucial (Crozier et al, 2022; Manohar et al, 2022; Wang et al, 2022) ( Supplementary Figure 4A ). Cells that enter S-phase and undergo replication stress will trigger a DNA damage response, which was demonstrated to activate NF-kappa-B and induce a secretory phenotype that promotes proliferation and migration of tumour cells (Chien et al, 2011; Rodier et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, we hypothesise that increased nuclear area, together with subscaling of DNA replication licensing factors ( Supplementary Table 1 ) (Crozier et al, 2022), could cause an overall decreased concentration of nuclear proteins leading to lower efficiency in DNA origin licensing. In addition, in recent work, it has been shown that cellular overgrowth makes cells more sensitive to DNA damage during the G0/G1 arrest (Manohar et al, 2022). This was, at least in part, attributed to a reduced capacity for p53 to respond to DNA damage occurring in these arrested cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, some cells can escape this G1 arrest, but these cells experience significant replication stress during the proceeding S-phase, which is associated with dilution of replisome components that subscale with size (Crozier et al, 2022a; Crozier et al, 2022b). Very recent data suggest that the DNA damage response is also impaired in enlarged cells, and the DNA itself may be prone to damage (Manohar et al, 2022). As a result of these replication-associated problems, p21 protein is induced again as cells enter G2, causing further cell cycle exit (Crozier et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these replication-associated problems, p21 protein is induced again as cells enter G2, causing further cell cycle exit (Crozier et al, 2022a). Finally, cells that fail to exit the cell cycle from G2, in particular p53-deficient cells that cannot induce p21, enter mitosis and experience even further damage due to catastrophic chromosome segregation errors, promoting further cell cycle withdrawals (Crozier et al, 2022a; Crozier et al, 2022b; Manohar et al, 2022; Wang et al, 2022). Future research will be important to determine how much these various routes to genotoxic stress contribute to cell cycle exit in cancer cells with different oncogenic mutations.…”
Section: Discussionmentioning
confidence: 99%